Expansion of the central arborizations of persistent sensory neurons during insect metamorphosis: the role of the steroid hormone, 20- hydroxyecdysone - Levine, RB (J Neurosci, 1989)
During insect metamorphosis many larval neurons persist but are modified to serve new behavioral roles at later stages of life. For example, certain larval mechanosensory neurons expand their central arborizations during pupal development and evoke a different behavioral response, the gin trap reflex. The role of the insect steroid hormone, 20-hydroxyecdysone (20-HE) in this developmental change was investigated by removing the normal source of the hormone, followed by topical application of 20-HE to the peripheral somata of the sensory neurons. In prepupal animals that were ligated between the abdomen and thorax to remove the source of ecdysteroids the sensory neurons retained a larval arborization pattern. Topical application of 20-HE to the peripheral sensory neuron somata caused the treated neurons to undergo terminal arbor expansion within the CNS. The treated sensory neurons were not able to evoke the normal pupal behavioral response, but instead caused a larval-like reflex response. In a previous study, sensory neurons that were treated peripherally with a juvenile hormone analog during the commitment peak of ecdysteroids were shown to retain a larval arborization pattern at pupation and to not evoke the gin trap reflex (Levine et al., 1986). Within 4 d of pupation, however, these neurons belatedly developed expanded terminal arbors and evoked the pupal reflex. In the present study, similarly treated animals were ligated at pupation to block the surge in ecdysteroids that normally occurs at this time. This treatment prevented both the delayed expansion and the reflex, whereas topical 20-HE application induced growth and allowed the treated sensory neurons to evoke the gin trap reflex. It is concluded that both 20-HE and juvenile hormone act directly on the cell bodies of the sensory neurons to regulate the growth of their central processes. This growth is necessary but not sufficient for the development of the gin trap reflex, suggesting that other steroid-dependent changes must also occur within the CNS. Thus, as in the vertebrates, steroid hormones direct important developmental events within the insect nervous system.